2001
DOI: 10.1029/2001jd000343
|View full text |Cite
|
Sign up to set email alerts
|

Open‐path Fourier transform infrared spectroscopy of SO2: An empirical error budget analysis, with implications for volcano monitoring

Abstract: Abstract. Fourier transform infrared (FTIR) spectroscopy is increasingly used as a tool forspectra of certified SO2 mixtures in order to assess the sensitivity of such instruments and the retrieval procedures used for field spectra. We investigate the effects on retrievals of the SO2 v•+v3 band (centered at 2499.87 cm ) of varying the retrieval spectral window and background fit, and of errors in the instrument line shape (ILS), temperature, and pressure. Largest deviations in retrieved amounts result from err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
54
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 21 publications
(2 reference statements)
1
54
0
Order By: Relevance
“…Independent studies quantifying the error budget of the gas concentration retrievals have estimated that for a SO 2 concentration of 250 ppm, the choice of the background polynomial and inaccuracies in the instrumental line shape account for an uncertainty of 1.2 and 1.5 %, respectively (Horrocks et al 2001). Similarly, Smith et al (2011) estimated that for a CO 2 concentration of 280 ppm, the choice of the polynomial and FOV variations of the instrument account for an uncertainty of 1.7 and 5.2 %, respectively.…”
Section: Ftir Measurementsmentioning
confidence: 99%
“…Independent studies quantifying the error budget of the gas concentration retrievals have estimated that for a SO 2 concentration of 250 ppm, the choice of the background polynomial and inaccuracies in the instrumental line shape account for an uncertainty of 1.2 and 1.5 %, respectively (Horrocks et al 2001). Similarly, Smith et al (2011) estimated that for a CO 2 concentration of 280 ppm, the choice of the polynomial and FOV variations of the instrument account for an uncertainty of 1.7 and 5.2 %, respectively.…”
Section: Ftir Measurementsmentioning
confidence: 99%
“…In these applications single field-ofview (FoV), medium-spectral-resolution (6-0.5 cm −1 ) interferometers are used to gather quantitative information on multiple gas species simultaneously. Fourier-transform interferometers (FT-IRs) have become a very valuable device for volcanic gas studies (Love et al, 1998;Oppenheimer et al, 1998;Burton et al, 2000;Horrocks, 2001), including measurements of gas ratios reported by Oppenheimer et al (2002). Systems using ultraviolet light as a source have recently been developed for volcanic SO 2 measurements (McGonigle, 2005;Horton et al, 2006), for volcanic BrO measurements (Bobrowski et al, 2003), and also for CO 2 slantpath columns (Goff et al, 2001).…”
mentioning
confidence: 99%
“…This value for total uncertainty seems to be high compared to active OP-FTIR investigations (Horrocks et al, 2001;Smith et al, 2011). The uncertainty in the temperature difference between background and considered atmospheric gas compound could be identified as the main error source for the passive measurements, and a threshold of 2 K for data filtering was defined.…”
Section: Uncertainty In Op-ftir Co 2 Measurementsmentioning
confidence: 99%
“…These doubts in the true ILS of the applied spectrometer can lead to uncertainties in smoothing of spectral information and later on in concentration determination errors. Horrocks et al (2001) estimated a concentration retrieval error of about 2 % due to an ILS uncertainty by measuring defined gas concentrations under fixed conditions. However, recent investigations concerning the sensitivity of OP-FTIR retrievals by Smith et al (2011) point out that using a broader spectral feature for concentration retrieval is suitable for the minimization of the effect of ILS on individual absorption lines.…”
Section: Uncertainty In Op-ftir Co 2 Measurementsmentioning
confidence: 99%
See 1 more Smart Citation